Harry Roberts and Foxtrot One-One : the Shepherd's Bush Massacre. - Barton, Geoffrey (Waterside Press, 2017)
In August 1966, two weeks after England won the World Cup, and four miles from Wembley Stadium, Harry Roberts and his associates gunned down three unarmed police detectives in front of dozens of primary school children. The nation was outraged and struggled to understand what had happened.